Ethnolinguistic revitalization of Slovene Minority in Hungary - Bernjak, Elizabeta (Anali PAZU, 2022)
The article focuses on an exploration of the historical and sociocultural reasons for the process of losing the minority mother tongue and ethnicity among the Slovene minority in Hungary. Based on empirical research, the author establishes that the main reasons for the replacement of minority language are the abandonment and limitation of its functions and the weakening of communicative ability in the mother tongue amongst minority members. Furthermore, the author introduces some aspects of planning for an ethnolinguistic revitalization of the minority community. She supports systematic planning for the status, corpus, prestige and usage of the minority tongue in public institutions, which would benefit the community in solving its direct communication and indirect economic problems.